Exploring Students’ Problem-Solving Skills Reviewed from Gender Perspective in Elementary School - Laely Farokhah; Dessy Norma Juita; Venna Puspita Sari; Muhammad Zulfadhli; Apit Dulyapit (Pedagogik Journal of Islamic Elementary School, 2026)
Mathematics education serves a fundamental role in developing students’ 21st-century competencies, particularly in fostering reasoning, communication, critical thinking, and problem-solving skills. However, instructional practices in elementary schools still tend to emphasize routine and procedural tasks, resulting in students’ limited exposure to non-routine problems that require higher-order thinking strategies. This study aims to explore elementary school students’ mathematical problem-solving skills reviewed from gender perspective. A qualitative research approach was employed. The data were collected through problem-solving skill tests, observations, interviews, and documentation, and subsequently analyzed using the Miles and Huberman model. The findings indicate that students with high problem-solving skill are able to carry out problem-solving steps in a coherent and systematic manner, although reinforcement is still needed in terms of accuracy and verification. In contrast, students with low problem-solving skill experience difficulties at almost all stages of the problem-solving process. These difficulties are characterized by insufficient conceptual understanding, inability to organize information, lack of proficiency in performing mathematical operations, and the absence of habits related to checking calculation results. Both male and female students demonstrate adequate basic problem-solving abilities. However, female students exhibit more structured, systematic, and detail-oriented thinking processes at each stage. In contrast, male students tend to be less consistent in utilizing all available information, rely more heavily on visual approaches, and show less accuracy in verifying their solutions. These findings highlight the necessity of designing mathematics instruction that prioritizes the development of problem-solving skills while incorporating an awareness of gender-based variations in students’ cognitive processing.